2013
DOI: 10.1002/oby.20001
|View full text |Cite
|
Sign up to set email alerts
|

Low‐density lipoprotein receptor‐related protein 1 variant interacts with saturated fatty acids in puerto ricans

Abstract: Low density lipoprotein related receptor protein 1 (LRP1) is a multi-functional endocytic receptor that is highly expressed in adipocytes and the hypothalamus. Animal models and in vitro studies support a role for LRP1 in adipocyte metabolism and leptin signaling, but genetic polymorphisms have not been evaluated for obesity in people. We examined whether dietary fats (eg., saturated, polyunsaturated) modulated the association of LRP1 variants with anthropometric traits. We studied a population-based sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…In both populations, the CC genotype was associated with a greater degree of obesity in those consuming a high SFA diet [185] 700 Iranian diabetic men and women/cross-sectional APOB v /Ins/Del SNP within the first exon A high n-3 PUFA consumption decreased the obesity risk in carriers of the Del allele of APOB gene [186] 920 Puerto Rican origin men and women/survey LRP1 w /rs1799986, rs715948, and rs1800191 A high intake of SFA was associated with a higher BMI, and higher waist and hip circumferences in carriers of rs1799986 T allele compared to CC. High palmitic and stearic acids induced the strongest effect on BMI mediates lipoprotein remnant uptake, is highly expressed in adipocyte, and has been suggested to play a role in adipogenesis, cell signaling, and energy and glucose metabolism SCAT [143,148].…”
Section: /Rs1800629mentioning
confidence: 99%
“…In both populations, the CC genotype was associated with a greater degree of obesity in those consuming a high SFA diet [185] 700 Iranian diabetic men and women/cross-sectional APOB v /Ins/Del SNP within the first exon A high n-3 PUFA consumption decreased the obesity risk in carriers of the Del allele of APOB gene [186] 920 Puerto Rican origin men and women/survey LRP1 w /rs1799986, rs715948, and rs1800191 A high intake of SFA was associated with a higher BMI, and higher waist and hip circumferences in carriers of rs1799986 T allele compared to CC. High palmitic and stearic acids induced the strongest effect on BMI mediates lipoprotein remnant uptake, is highly expressed in adipocyte, and has been suggested to play a role in adipogenesis, cell signaling, and energy and glucose metabolism SCAT [143,148].…”
Section: /Rs1800629mentioning
confidence: 99%
“…The differences revealed in this study have genetic and biologic plausibility given the findings from several recent studies in the Hispanic population which demonstrated distinct polymorphisms in genes involved in lipid metabolism depending on the cultural and ancestral background of the patients (2730). For example, using population structure analysis of 1,374 unrelated Hispanic individuals from the Multi-Ethnic Study of Atherosclerosis (MESA) Manichaikul et al identified at least four genetically distinct groups within the so called “Hispanic” population: Central/South America, the Dominican Republic and Cuba, Mexico, and Puerto Rico.…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, we did not replicate an interaction between SFA and a second LRP1 variant (rs1799986) that was observed in a separate study of Boston Puerto Ricans. 26 Neither of these two previous single population studies analyzed rs2306692, the variant that showed statistically significant interaction with SFA intake for anthropometric traits in our meta-analysis of data from four studies. Inconsistencies in genetic association studies are common, and may be attributed to undetected environmental interactions, differences in confounding variables or false-positive results obtained in single populations.…”
Section: Discussionmentioning
confidence: 89%
“…One study reported the association of LRP1 rs715948 genotype with body mass index (BMI) in US whites 25 and a second documented an interaction between LRP1 rs1799986 and diet, in which saturated fat intake modulated anthropometric traits in US Puerto Ricans. 26 Notably, each of these previous studies was limited to a single population. Although data supporting a role of LRP1 variants in obesity are accumulating, investigations that include interaction analyses in additional populations are warranted.…”
Section: Introductionmentioning
confidence: 99%